2010
DOI: 10.1161/circulationaha.109.931691
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arrest Transnasal Evaporative Cooling

Abstract: Background-Transnasal evaporative cooling has sufficient heat transfer capacity for effective intra-arrest cooling and improves survival in swine. The aim of this study was to determine the safety, feasibility, and cooling efficacy of prehospital transnasal cooling in humans and to explore its effects on neurologically intact survival to hospital discharge. Methods and Results-Witnessed cardiac arrest patients with a treatment interval Յ20 minutes were randomized to intra-arrest cooling with a RhinoChill devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
154
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 345 publications
(163 citation statements)
references
References 33 publications
0
154
1
2
Order By: Relevance
“…Animal models demonstrate that, earliest the hypothermia is initiated, the most beneficial effect is on neurological outcome. In human models, there are conflicting results: it seems that hypothermia remains beneficial even if delayed [16,17] . Therefore, there are still ongoing investigations to evaluate the effect of the delay of initiation of hypothermia in CA management.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models demonstrate that, earliest the hypothermia is initiated, the most beneficial effect is on neurological outcome. In human models, there are conflicting results: it seems that hypothermia remains beneficial even if delayed [16,17] . Therefore, there are still ongoing investigations to evaluate the effect of the delay of initiation of hypothermia in CA management.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53] Directly or indirectly, this led to an increased emphasis on EMS initiation of cooling in the field immediately following ROSC. 54,55 Recently, the conversation around the optimal use of therapeutic hypothermia has intensified with two large randomized trials failing to show a survival advantage for cooled patients. Nielsen et al examined the influence of cooling post-arrest patients to 36°C (96.8°F) instead of 33°C (91.4°F) and noted that survival was similar between groups.…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
“…In 2002, 2 key studies 25,26 showed that treatment with 27 and the AHA 28 recommended induced hypothermia in post-cardiac arrest patients with ROSC who remain comatose ( Table 2). Prehospital cooling studies 29,30 have also been performed; however, no clear evidence shows that prehospital cooling is advantageous, and ongoing investigations continue. Induced hypothermia should be initiated to a target temperature of 32ºC to 34ºC as quickly as possible and within 6 to 12 hours for patients who are unable to follow verbal commands after ROSC.…”
Section: Management Of Post-cardiac Arrest Syndromementioning
confidence: 99%